2008
DOI: 10.1021/ac801980b
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Biomineralization Using Microfluidics

Abstract: Biomineralization is the process where biological systems produce well-defined composite structures such as shell, teeth, and bones. Currently, there is substantial momentum to investigate the processes implicated in biomineralization and to unravel the complex roles of proteins in the control of polymorph switching. An understanding of these processes may have wide-ranging significance in health care applications and in the development of advanced materials. We have demonstrated a microfluidic approach toward… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…The continuous flow microfluidic system was also associated with a wide distribution of crystals sizes. This has been observed previously for calcium carbonate 21,22 and is unavoidable due to the residence time distributions associated with continuous-flow operation. Importantly, segmented flow reactions do not suffer from such limitations as droplets do not interact with channel walls and therefore move at a constant linear velocity, eliminating residence time distributions.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The continuous flow microfluidic system was also associated with a wide distribution of crystals sizes. This has been observed previously for calcium carbonate 21,22 and is unavoidable due to the residence time distributions associated with continuous-flow operation. Importantly, segmented flow reactions do not suffer from such limitations as droplets do not interact with channel walls and therefore move at a constant linear velocity, eliminating residence time distributions.…”
Section: Discussionsupporting
confidence: 65%
“…To date, the only microfluidic approach reported for the synthesis of calcium carbonate has involved continuous-flow mixing of reagents at a T-junction. 21,22 These proof-of-principle studies demonstrated facile crystal formation, and extraction of crystals for off-chip characterization by scanning electron microscopy (SEM) showed predominantly calcite polymorphs present. Unfortunately, the unavoidable residence time distributions associated with continuous-flow reactors significantly reduce control over reaction times, leading to broad size distributions of the resulting crystals and therefore limited control over the crystal polymorph.…”
Section: Introductionmentioning
confidence: 85%
“…Recently we have demonstrated the potential of microfluidics as a new platform for understanding biomineralisation. 19 Many advantages of microfluidics over bulk systems have been demonstrated such as fast analysis, small sample consumption and excellent reproducibility. 20,21 These advantages have been exploited in life sciences e.g.…”
Section: This Journal Is C the Royal Society Of Chemistry 2010mentioning
confidence: 99%
“…25,26 Real time growth of CaCO 3 crystals in the presence of EP extracts was monitored on-chip with in situ Raman microspectroscopy to determine the resultant crystal polymorph. 19 Here we look specifically at the calcium-binding activity of the most abundant EP protein. We demonstrate the power of microfluidics to probe the complex factors that control biomineralisation, providing insight into the influence of this specific protein that cannot be obtained from experimental crystal growth in bulk solutions.…”
Section: This Journal Is C the Royal Society Of Chemistry 2010mentioning
confidence: 99%
See 1 more Smart Citation